Balloon Catheter for Cervical Priming before Operative Hysteroscopy in Young Women: A Pilot Study. Issue 4 (20th April 2020) - Falcone, Francesca; Raimondo, Gennaro; Stark, Michael; Dessole, Salvatore; Torella, Marco; Raimondo, Ivano
Abstract: Aim : To investigate regarding the safety and effectiveness of a balloon catheter (Aqueduct-100 device) to dilate the uterine cervix before operative hysteroscopies. Secondary objectives were to evaluate the duration of the dilatation procedure and to investigate on physicians' satisfaction with the device. Methods : Fifty women younger than 40 years, wishing pregnancies and diagnosed with apparently benign intrauterine lesions and/or uterine anomalies, were enrolled into this study and submitted to cervical priming with Aqueduct-100 device before operative hysteroscopy. Results : Initial cervical dilatation was ≤4 mm in all but one patient. Adequate (10 mm) cervical dilatation was achieved in only one patient, the remaining forty-nine needed additional cervical dilatation. All women, however, presented with a ≥6 mm cervical width after balloon catheter removal. The mean time to final cervical dilatation was 8.5 minutes. No perioperative complications occurred. Physicians reported, in the majority of cases, satisfaction for the dilatation achieved (66%), the ease of balloon catheter insertion/use (82%), and for the ease of additional dilatation (96%). Conclusions : Aqueduct-100 device before operative hysteroscopy is safe and useful to increase the baseline cervical width and facilitate additional dilatation, with good effects on physician satisfaction and acceptable dilatation times.